DEVELOPMENT OF POETRY TEACHING MATERIALS BASED ON CREATIVE PROCESS - Kusmana, Suherli (Sanata Dharma University Yogyakarta, 2020)
This study aims to overcome the problem of the quality of Indonesian language learning outcomes in high schools (SMA), especially the topic of poetry texts which are still low. The results of this study are intended to assist the government in improving the quality of the implementation of the 2013 curriculum at the high school level. The weakness of applying the 2013 curriculum is the limitations of teaching materials, including poetry text teaching materials. Learning this material is expected to encourage students to express their thoughts, feelings, and ideas through beautiful, rhythmic language, literary values but not offending others. The method used in this research is research and development with five selected literary writers who are productive in producing poetry texts. Next, in testing the developed teaching material, students from SMA Negeri 1 Manonjaya Tasikmalaya were chosen. Teaching material developed based on the poet's creative process in producing literary works of poetry text is combined with the composition of basic competencies based on the curriculum with scientific presentation. Teaching material which is evaluated based on content, presentation, language, and graphic criteria by academics and practitioners meets the eligibility criteria as teaching material in high school. Based on the testing of the application of teaching materials, it was found that the teaching materials were able to encourage students to produce quality poetry texts. Indonesian Language learning also takes place effectively in achieving goals.DOI: 10.24071/ijiet.2020.040113